Madhesh Province’s Examination System of Nepal: Problems and Difficulties - Yadav, Durga Kumari; Thapa, Yogendra; Yadav, Chandradip Kumar; Shahi, Neelam; Bhattarai, Ajaya (Damak Campus Journal, 2024)
The main difficulties and problems with the examination system in Nepal’s Madhesh Province are attempted to be brought up in this article. The entire educational system, including the curriculum, lecturers, instructional materials, and methodology, is intimately related to the examination system.The paper makes a strong case that the dualistic educational system, exclusion of local cultures, languages, and knowledge from the curriculum, pedagogy, and exams, lack of enough trained and qualified teachers, use of transmission-oriented pedagogy, and holding only three-hour paper-pencil tests to gauge students’ intelligence once a year are the main obstacles to quality education in Madhesh Province, Nepal. Lack of access to high-quality education results in an undereducated workforce, increased rates of unemployment and poverty, war and violence, and perpetuation of prejudice, injustice, and inequality in Nepal’s larger Madhesh Province society.This article aims to explore the problems and difficulties surrounding the examination system in the province, highlighting the socio-economic, infrastructural, and administrative barriers that hinder the system’s success.